Serum C peptide and carotid intima-medial thickness are independent markers of glucose intolerance among patients with ischemic cerebrovascular stroke - Nearmeen M Rashad; Ghada M Samir; Hanan M Sabry; Nesreen M Mohy; Shereen M El Shabrawy (SpringerOpen, 2019)
Background Stroke is the most common cause of disability worldwide. C-peptide is co-secreted with insulin from beta cells of the pancreas, thus providing a better index of endogenous insulin production and pancreatic beta cell function. The objective of the current study was to explore serum C-peptide and carotid intimamedia thickness in patients with ischemic stroke (IS) and to assess the association of serum C-peptide with vascular and metabolic risks. Patients and methods The case-control study included 50 healthy control and 150 patients with IS who were stratified into three subgroups according to their fasting plasma glucose, normal glucose tolerance (NGT), impaired glucose tolerance (IGT), and type 2 diabetes mellitus (T2DM). All the participants were subjected to B-mode ultrasonography of both common carotid arteries to measure carotid intimamedia thickness (mm). Serum C peptide concentration was measured by enzyme-linked immunosorbent assay. Results Serum C peptide levels were higher in IS patients compared with control. Among the IS patients, C peptide was higher in T2DM compared with IGT and NGT and is associated with vascular and metabolic risks, after adjusting for the traditional risk factors. C-peptide was a statistically significance predictor of T2DM among IS patients by the logistic regression analysis test. In addition, homeostasis model assessment of insulin resistance (HOMA-IR), fasting plasma glucose, BMI, and fat mass index (FMI)% were independently correlated with C-peptide by. The diagnostic value of C-peptide by receiver operating characteristic curves was highly significant; the sensitivities and the specificities were 96 and 98%. Conclusion Serum peptide levels were higher in IS patients compared with the control. Among the IS patients, serum C peptide was higher in T2DM compared with IGT and NGT and is associated with vascular and metabolic risks.